Introduction of Unaccusative Verbs in the Spanish as a Foreign Language Classroom - Yang, Ming (2019)
Verbal transitivity always supposes a great difficulty for Chinese students of Spanish as a foreign language (SFL). Verbs with unstable valency behavior cause confusion. According to traditional grammar, there are transitive, intransitive, or impersonal verbs. The Unaccusative Hypothesis (Perlmutter, 1971) classifies intransitive verbs as unaccusative or unergative. In this article, we propose that word order of the subject and predicate, and the absolute passive participle structure and middle voice in Spanish, can be understood more easily with the introduction of the concept of unaccusative verbs analyzed with the lexical-syntactic interface, thus offering a new perspective for the teaching of SFL to Chinese students.